2015
DOI: 10.1249/mss.0000000000000630
|View full text |Cite
|
Sign up to set email alerts
|

“Live High–Train Low and High” Hypoxic Training Improves Team-Sport Performance

Abstract: "Live high-train low and high" hypoxic training interspersed with repeated sprints in hypoxia for 14 d (in season) increases the Hbmass, YYIR2 performance, and repeated-sprint ability of elite field team-sport players, with benefits lasting for at least 3 wk postintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
116
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(129 citation statements)
references
References 26 publications
7
116
1
5
Order By: Relevance
“…Computation of YYIR2 test global means, SDs and quantiles (Figure 3) involved 116 studies/subgroups reporting on 2,478 participants (median age = 23.2 years, IQR = 20.7–26.0 years) (Young et al, 2005; De Souza et al, 2006; Krustrup et al, 2006; Thomas et al, 2006; Mohr et al, 2007, 2016; Iaia et al, 2008, 2015, 2017; Morton et al, 2009; Rampinini et al, 2010; Rebelo et al, 2010; Thomassen et al, 2010; Christensen et al, 2011; Chuman et al, 2011; Mooney et al, 2011, 2013a,b; Roberts et al, 2011; Ueda et al, 2011; Gunnarsson et al, 2012; Ingebrigtsen et al, 2012, 2013, 2014; Nakamura et al, 2012; Saunders et al, 2012; Wells et al, 2012, 2014; Bassini et al, 2013; Buchheit et al, 2013; McGawley and Andersson, 2013; Mohr and Krustrup, 2013, 2014, 2016; Owen et al, 2013; Pivovarniček et al, 2013; Yuki et al, 2013; Fanchini et al, 2014; Karavelioglu et al, 2014; Lollo et al, 2014; Miloski et al, 2014; Nunes et al, 2014; Sampaio et al, 2014; Skovgaard et al, 2014; Brocherie et al, 2015a,b; Cholewa et al, 2015; Coelho et al, 2015; Gatterer et al, 2015; Hogarth et al, 2015a,b; Jamurtas et al, 2015; Krustrup and Mohr, 2015; Leme et al, 2015; Mara et al, 2015; Matta et al, 2015; McLean et al, 2015; Michalsik et al, 2015; Mohr, 2015; Rogan, 2015; Stein et al, 2015; Boer and Van Aswegen, 2016; Bouaziz et al, 2016; Chan et al, 2016; Inness et al, 2016; Joo, 2016; Kilit and Arslan, 2016; Lockie et al, 2016a,b,...…”
Section: Resultsmentioning
confidence: 99%
“…Computation of YYIR2 test global means, SDs and quantiles (Figure 3) involved 116 studies/subgroups reporting on 2,478 participants (median age = 23.2 years, IQR = 20.7–26.0 years) (Young et al, 2005; De Souza et al, 2006; Krustrup et al, 2006; Thomas et al, 2006; Mohr et al, 2007, 2016; Iaia et al, 2008, 2015, 2017; Morton et al, 2009; Rampinini et al, 2010; Rebelo et al, 2010; Thomassen et al, 2010; Christensen et al, 2011; Chuman et al, 2011; Mooney et al, 2011, 2013a,b; Roberts et al, 2011; Ueda et al, 2011; Gunnarsson et al, 2012; Ingebrigtsen et al, 2012, 2013, 2014; Nakamura et al, 2012; Saunders et al, 2012; Wells et al, 2012, 2014; Bassini et al, 2013; Buchheit et al, 2013; McGawley and Andersson, 2013; Mohr and Krustrup, 2013, 2014, 2016; Owen et al, 2013; Pivovarniček et al, 2013; Yuki et al, 2013; Fanchini et al, 2014; Karavelioglu et al, 2014; Lollo et al, 2014; Miloski et al, 2014; Nunes et al, 2014; Sampaio et al, 2014; Skovgaard et al, 2014; Brocherie et al, 2015a,b; Cholewa et al, 2015; Coelho et al, 2015; Gatterer et al, 2015; Hogarth et al, 2015a,b; Jamurtas et al, 2015; Krustrup and Mohr, 2015; Leme et al, 2015; Mara et al, 2015; Matta et al, 2015; McLean et al, 2015; Michalsik et al, 2015; Mohr, 2015; Rogan, 2015; Stein et al, 2015; Boer and Van Aswegen, 2016; Bouaziz et al, 2016; Chan et al, 2016; Inness et al, 2016; Joo, 2016; Kilit and Arslan, 2016; Lockie et al, 2016a,b,...…”
Section: Resultsmentioning
confidence: 99%
“…From a practical point of view, Gatterer et al (2014) demonstrated that completing shuttle runs in the confined space of a hypoxic chamber is a viable option to gain the benefits of RSH while maintaining movement specificity. Brocherie et al (2015) recently used this strategy with success, demonstrating that elite hockey players completing over-ground running RSH in an inflatable hypoxic marquee were able to improve and maintain repeated sprint ability for at least 3 weeks after a RSH intervention. This is critical, as previous researchers have identified limited crossover effects of RSH between cycling and running modalities (Goods et al, 2015).…”
Section: Recommendations and Considerationsmentioning
confidence: 99%
“…Additionally, as proposed for IHRT, short incomplete recoveries via exaggerated work:rest ratios (1:2–1:3) may be more successful for increasing glycolytic stress and therefore performance outcomes (Faiss et al, 2013b) than protocols employing work:rest ratios more commonly used for repeated sprint ability tests (1:5+) (Goods et al, 2015). Nevertheless, it must be acknowledged that some studies have reported varied effects of RSH on metabolic adaptation and performance improvements (Galvin et al, 2013; Brocherie et al, 2015; Goods et al, 2015). Further research is therefore needed to provide conclusive recommendations regarding RSH implementation.…”
Section: Recommendations and Considerationsmentioning
confidence: 99%
“…Among these methods, LHTL intervention is widely recognized as the “gold standard” for normoxic exercise performance in athletes 2, 22 . …”
Section: Introductionmentioning
confidence: 99%
“…These training effects lead to improved maximal oxygen consumption (VO 2max ) and oxygen flux rates during exercise 2, 3, 8 . The optimal “dose” of hypoxia is a very important issue for the successful LHTL intervention outcomes of athletic performance.…”
Section: Introductionmentioning
confidence: 99%